Filamentous fungal infections of the cornea: a global overview of epidemiology and drug sensitivity. Issue 4 (27th February 2015) - Kredics, László; Narendran, Venkatapathy; Shobana, Coimbatore Subramanian; Vágvölgyi, Csaba; Manikandan, Palanisamy; Indo‐Hungarian Fungal Keratitis Working Group
Summary Fungal keratitis is a serious suppurative, usually ulcerative corneal infection which may result in blindness or reduced vision. Epidemiological studies indicate that the occurrence of fungal keratitis is higher in warm, humid regions with agricultural economy. The most frequent filamentous fungal genera among the causal agents are Fusarium, Aspergillus and Curvularia. A more successful therapy of fungal keratitis relies on precise identification of the pathogen to the species level using molecular tools. As the sequence analysis of the internal transcribed spacer (ITS) region of the ribosomal RNA gene cluster (rDNA) is not discriminative enough to reveal a species‐level diagnosis for several filamentous fungal species highly relevant in keratitis infections, analysis of other loci is also required for an exact diagnosis. Molecular identifications may also reveal the involvement of fungal species which were not previously reported from corneal infections. The routinely applied chemotherapy of fungal keratitis is based on the topical and systemic administration of polyenes and azole compounds. Antifungal susceptibility testing of the causal agents is of special importance due to the emergence and spread of resistance. Testing the applicability of further available antifungals and screening for new, potential compounds for the therapy of fungal keratitis are of highlighted interest.